LAND USE, TAMBAK OWNERSHIP, AND TAMBAK CULTIVATION A CASE STUDY OF “SUMBERSARI” IN NORTH CENTRAL JAVA - Nurdien H. Kistanto (JOURNAL OF COASTAL DEVELOPMENT, 2001)
The establishment of the plywood factory in “Sumbersari” has changed the pattern of land use. As in many other north coast villages along the Java Sea, agricultural land can be divided into two major categories, namely tambak (brackishwater ponds used for aquaculture) and sawah (irrigated land used for wet-rice cultivation). Landholders may thus own tambak and/or sawah. Tambak can be further divided into tambak bandeng (milkfish brackishwater pond) and tambak udang bago (giant-tiger shrimp brackishwater pond). Both can be farmed alone or they can be combined, which is locally called tambak campuran (mixed brackishwater pond). Tambak bandeng are sometimes further differentiated from tambak ipukan (fry pond), a smaller type of tambak designed for nursing milkfish fry to fingerlings. Still another type of tambak, which is only a portion of an irrigation stream or canal where landless peasants trap fish and shrimp with a bamboo fence, locally called tambak kali (canal pond).